Legal Protection for Illegal Loan Customers: Analysis Based on Personal Data Protection Law - Adi Kurniawan; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2023)
This research aims to analyze the legal protection available to customers of illegal online loans, with a focus on the aspect of personal data protection. The proliferation of illegal online lending has created vulnerabilities to the security and privacy of customers' personal data. The personal data protection law is a relevant legal instrument in providing protection against the collection, use and storage of personal data by illegal online loan providers. This research uses a normative analysis approach by referring to laws and regulations, court decisions, and related literature. The data obtained is analyzed descriptively to obtain a comprehensive understanding of the existing legal framework. The results show that the personal data protection law can provide a legal basis for customers of illegal online loans to protect the privacy and security of their personal data. However, the implementation of this law still has significant challenges. One of the main challenges is effective law enforcement against personal data protection violations committed by illegal online loan providers.